O źródłach dobrych instytucji i makroekonomicznej stabilności: ekonomia polityczna szwedzkiego kryzysu 2008—2009 - Czech, Sławomir (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: Sound institutions and macroeconomic stability: the political economy of the Swedish 2008—2009 recession. Global recession that started in 2007 brought economic downturn experienced by almost all highly developed countries. Its consequences consisted not only of the slump in terms of national income and further GDP stagnation, but also of instability of public finance in many countries. This paper analyses the case of Sweden, which performed relatively well through the crisis and managed to keep public finances stable. As it seems, it was not a coincidence, but a lesson learned from the previous crisis which closely resembles the recession of 2008. By showing this relation we wish to demonstrate how strong the ties between the sphere of economy and politics are, which is unfortunately often disregarded by mainstream economics. In fact, political economy copes with this task much better. Key words: political economy, institutions, economic crises, political and economic order, macroeconomic stability.